Synergistic influence of collagen I and BMP 2 drives osteogenic differentiation of mesenchymal stem cells: A cell microarray analysis. (1st April 2016) - Rasi Ghaemi, Soraya; Delalat, Bahman; Cetó, Xavier; Harding, Frances J.; Tuke, Jonathan; Voelcker, Nicolas H.
Graphical abstract: Abstract: Cell microarrays are a novel platform for the high throughput discovery of new biomaterials. By re-creating a multitude of cell microenvironments on a single slide, this approach can identify the optimal surface composition to drive a desired cell response. To systematically study the effects of molecular microenvironments on stem cell fate, we designed a cell microarray based on parallel exposure of mesenchymal stem cells (MSCs) to surface-immobilised collagen I (Coll I) and bone morphogenetic protein 2 (BMP 2). This was achieved by means of a reactive coating on a slide surface, enabling the covalent anchoring of Coll I and BMP 2 as microscale spots printed by a robotic contact printer. The surface between the printed protein spots was passivated using poly (ethylene glycol) bisamine 10, 000 Da (A-PEG). MSCs were then captured and cultured on array spots composed of binary mixtures of Coll I and BMP 2, followed by automated image acquisition and quantitative, multi-parameter analysis of cellular responses. Surface compositions that gave the highest osteogenic differentiation were determined using Runx2 expression and calcium deposition. Quantitative single cell analysis revealed subtle concentration-dependent effects of surface-immobilised proteins on the extent of osteogenic differentiation obscured using conventional analysis. In particular, the synergistic interaction of Coll I and BMP 2 in supporting osteogenic differentiation was confirmed. Our studies demonstrate the value of cell microarray platforms to decipher the combinatorial interactions at play in stem cell niche microenvironments.